KAJIAN HUKUM TENTANG TANGGUNG JAWAB ADMINISTRASI RUMAH SAKIT TERHADAP KESELAMATAN DAN KESEHATAN KERJA DITINJAU DARI PERATURAN MENTERI KESEHATAN NOMOR 66 TAHUN 2016 TENTANG KESELAMATAN DAN KESEHATAN KERJA RUMAH SAKIT - sinatra Gunawan (Yuriska: Jurnal Ilmiah Hukum, 2018)
Health and Safety of Hospital Work (K3RS) is the application of UUD 1945 chapter 27 verse (2) and Chapter 28 H and Health Ministry’s Regulation number 66 2016. K3 has existed since long time ago and its application has been less satisfactory as this was proven by UU number 1 1970 about Work Safety and UU number 44 2009 about Hospital. The application of K3RS is one of the actions taken to ensure and protect the safety and health of the human resources of the hospital, patients, nurses, visitors, and its environment as well as its physical condition. Health Ministry’s Regulation Number 66 2016 specifically describes about K3RS but there is no clear and detail description on what the hospital’s responsibilities are along with their consequences.The problem studied is related to the administrative responsibilities of the hospital along with their consequences for not executing Health Ministry’s Regulation Number 66 2016 in terms of K3RS. Method used for this law research is Normative Jurisdictive with referential and field study as the data collection technique. The writer did the research by looking for and collecting secondary data, compiled, described, and then analyzed in order to form a systematic, factual, and accurate description of the facts, characteristics or multi-phenomenon relationship studied. Data were analyzed qualitatively and the conclusion was drawn from there which later became the answer of the problem of this research.From the findings of the research, it was proven that there wasn’t optimum administrative responsibilities of the hospital and there were neither consequences addressed in written nor in person form in regards of why the K3RS was not implemented. The conclusion was drawn from this research was the administrative responsibilities of the hospital related to K3RS were not continuously applied and the written consequences form of the Health Ministry’s Regulation was not strict.